KONFLIK AGRARIA DAN PELEPASAN TANAH ULAYAT (STUDI KASUS PADA MASYARAKAT SUKU MELAYU DI KESATUAN PEMANGKUAN HUTAN DHARMASRAYA, SUMATERA BARAT) - Abdul Mutolib; Yonariza Yonariza; Mahdi Mahdi; Hanung Ismono (Jurnal Penelitian Sosial dan Ekonomi Kehutanan, 2015)
The conflict of  forest management in Indonesia is increasing. Forest management conflicts often caused by legal pluralism between government and society.  This study aims to describe the land conflicts between Melayu tribe community with government and communal land release process in Melayu tribe in Dharmasraya Forest Management Unit ( MU). Research method  Production PF was using descriptive qualitative. The study was conducted in FMU in Nagari Bonjol, Koto Besar Dharmasraya Regency. results showed that 1) Agrarian conflict in FMU Dharmasraya between community and the government occured due to the recognition of  legal pluralism in the forest, and 2) Communal land release occured through the buying and selling which  controlled by Datuak process of are customary authorities.  Evidence of  trading activities  the issuance of  "alas hak" as a sign that the communal land are controlled by has been sold. The of trading activities of  communal land were communal land and the high public interest to increase due to low prices of plant in communal land owned by Melayu tribe.  Some strategies are required to maintain the function of  forests in PFMU that has been acquired by local communit  without  local communities who depend on forestsy neglecting.